2008
DOI: 10.2478/s11687-008-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Note on morphology of two nematode species Ascaridia hermaphrodita and Ascaridia platyceri (Nematoda): scanning electron microscope study

Abstract: SummaryMorphological features of adult specimens of Ascaridia hermaphrodita and A. platyceri (Nematoda: Ascaridida), parasitizing parrots (Psittaciformes), were studied for the first time using scanning electron microscopy. The morphology of A. hermaphrodita, the type species of Ascaridia, coincides fully with the generic diagnosis. The shape of the labial inner structure (two spoon-like projections), cervical alae and spicule with cuticular wings were typical for this species. A. hermaphrodita has been found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Seven species of the genus Ascaridia Dujardin, 1845 (Nematoda: Ascaridiidae) have been reported from the order Psittaciformes. Among these, A. hermaphrodita is one of the most frequently reported in these birds (HODOVÁ et al, 2008). Previously, heavy infections of A. hermaphrodita were found in two female slender-billed parakeets that died at the Chilean National Zoo in Santiago (GONZÁLEZ-ACUÑA et al, 2007).…”
Section: Nematodamentioning
confidence: 99%
See 1 more Smart Citation
“…Seven species of the genus Ascaridia Dujardin, 1845 (Nematoda: Ascaridiidae) have been reported from the order Psittaciformes. Among these, A. hermaphrodita is one of the most frequently reported in these birds (HODOVÁ et al, 2008). Previously, heavy infections of A. hermaphrodita were found in two female slender-billed parakeets that died at the Chilean National Zoo in Santiago (GONZÁLEZ-ACUÑA et al, 2007).…”
Section: Nematodamentioning
confidence: 99%
“…Previously, heavy infections of A. hermaphrodita were found in two female slender-billed parakeets that died at the Chilean National Zoo in Santiago (GONZÁLEZ-ACUÑA et al, 2007). This parasite is considered one of the most common parasites found among parrots in captivity (HODOVÁ et al, 2008), likely due to the characteristics of this parasite's life cycle (direct cycles) and the high resistance of its eggs (ATKINSON et al, 2008). Hartwich & Tscherner (1979) also recorded A. platyceri in a captive Austral parakeet in Germany.…”
Section: Nematodamentioning
confidence: 99%
“…hermaphrodita was the most frequent parasite. Hodová et al (2008) reported that five species of Ascaridia are frequent in Psittaciformes; A. platyceri and A. hermaphrodita are the most common. In Brazil, Pinto et al (1993) reported A. hermaphrodita as specific of psittacines of genuses Amazona, Anodorhynchus, Ara, Aratinga, Brotogeris, Conurus, Pyrrhura, Psittacus and Pionus; this fact corroborates studies on psittacines in Argentina, Chile and Peru (MARTÍNEZ et al, 2003;MASELLO et al, 2006;GONZÁLEZ-ACUÑA et al, 2007;GÓMEZ-PUERTA et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ritchie et al (1994) reported that ascariasis stands out as one of the most common gastrointestinal parasitic infections in psittacines and is associated with clinical signs such as weight loss, anorexia and, in severe cases, death. González-Acuña et al (2007) and Hodová et al (2008) reported intestinal obstruction by A. hermaphrodita as a cause of death in parrots. Hodová et al (2008) obtained 242 specimens of helminths in necropsied psittacines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation